The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Paleomicrobiology 2008
DOI: 10.1007/978-3-540-75855-6_6
|View full text |Cite
|
Sign up to set email alerts
|

Palaeomicrobiology of Tuberculosis

Abstract: The study of tuberculosis palaeomicrobiology has proved to be most rewarding. Due to the characteristic palaeopathological lesions, tuberculosis was recognised in archaeological material and was the first infectious disease to be studied by modern biomolecular methods. The combination of a tough bacterial cell wall and GC-rich DNA has resulted in excellent DNA preservation in some specimens. A wide range of specific molecular diagnostic and typing methods, developed by clinical microbiologists, are available. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 101 publications
(90 reference statements)
0
17
0
Order By: Relevance
“…These early studies confirmed TB in Byzantine Turkey, pre-European contact Borneo, and a pre-Columbian Andean mummy (1000 BP). They were quickly followed by reports of MTBC aDNA in ancient Egypt, China, America, and Europe, summarized in a series of reviews [18,[25][26][27][28][29].…”
Section: Early Biomolecular Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…These early studies confirmed TB in Byzantine Turkey, pre-European contact Borneo, and a pre-Columbian Andean mummy (1000 BP). They were quickly followed by reports of MTBC aDNA in ancient Egypt, China, America, and Europe, summarized in a series of reviews [18,[25][26][27][28][29].…”
Section: Early Biomolecular Studiesmentioning
confidence: 98%
“…The early development of this field in archaeology and palaeontology had a strong influence on the initial criteria that emerged regarding the precautions required for the production of verifiable data based on aDNA [16,17]. These have since been modified [18] to take account of our increased understanding of the sources of contamination [19] and the stability of Mycobacterium tuberculosis complex (MTBC) aDNA [20] as compared with other biomolecules [21,22].…”
Section: Early Biomolecular Studiesmentioning
confidence: 99%
“…For millennia, tuberculosis (TB) remains a public health problem [1][2][3] . Between 2000 and 2015, at the global level, 49 million patients survived through strategies that sought greater performance in TB diagnosis and treatment in high-burden countries.…”
mentioning
confidence: 99%
“…Based on molecular analysis, the prevalence of TB was skeletal material dated to different centuries, and spinal TB was diagnosed in four cases 21 (Donoghue et al, 2008;Éry et al, 2008a, 2008b. Another case of spinal TB was described in 22 material from Zalavár-Vár (Acsádi et al, 1962).…”
mentioning
confidence: 99%